Deforestation, fires, and lack of governance are displacing thousands of jaguars in Brazilian Amazon. Issue 8 (25th June 2021) - Menezes, Jorge F. S.; Tortato, Fernando R.; Oliveira‐Santos, Luiz G. R.; Roque, Fabio O.; Morato, Ronaldo G.
Abstract: The rate of deforestation and the number of large wildfires are increasing in the Amazon. Illegal loggers, miners, ranchers, and farmers all have contributed to this increase. Their activities have dramatic consequences for biodiversity, ecological services, and people. In this study, we estimated the number of jaguars affected by deforestation. We focused on the Brazilian Amazon from August 2016 to December 2019. Further, we analyzed the effects of socio‐geographic determinants of deforestation and state policies. To do so, we used deforestation data from DETER‐B satellite system. The number of jaguars within each deforested area was pulled from a previous study, which provided jaguar abundances for jaguar entire range. We assumed all jaguars within a deforested area were affected (displaced or killed). To determine the underlying causes of jaguar loss, we regressed the number of jaguars lost per state and year against the proportion of total forest area within reserves, distance to forest border, and monetary efficiency in cattle production. We estimate a total of 1, 422 jaguars have been displaced/killed in recent years (2016: 488, 2017: 360, 2018: 268, 2019: 354). Only the proportion of protected area had an effect in reducing jaguar deforestation. We discuss how our work could result in near real‐time monitoring of jaguar displacement and how policies such as wood certification, more efficient cattle production, and centralizing governance may be solutions.